PENGARUH PRICE TERHADAP ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE SERTA TERHADAP REPURCHASE INTENTION KONSUMEN KOPI LOKAL KEKINIAN (KOPI TUKU DI JAKARTA) - Ilham Rafii Priyambodo; Mohammad Rizan; Nofriska Krissanya (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the influence of price on electronic word of mouth (E-WOM) and brand image, and their effects on repurchase intention among consumers of contemporary local coffee, focusing on Kopi Tuku in Jakarta. Using a quantitative approach, data were collected via an online questionnaire from 287 respondents who had purchased Kopi Tuku at least five times in the past three months, lived in Jakarta, were over 17 years old, and actively used the internet and social media to obtain information about the brand. The data were analyzed using Structural Equation Modeling (SEM) with Lisrel 8.8 software. Results indicate that price has a significant positive direct effect on E-WOM, brand image, and repurchase intention. Furthermore, E-WOM positively influences both brand image and repurchase intention. These findings support the Stimulus-Organism-Response (SOR) theory, suggesting that price as a stimulus affects internal consumer perceptions (E-WOM and brand image), which in turn impact repurchase intention as the consumer’s response. This research contributes theoretically by enhancing understanding of consumer behavior in the local coffee market and offers practical recommendations for Kopi Tuku’s management to optimize pricing strategies, strengthen brand image, and encourage positive E-WOM to improve customer loyalty and sales. The study provides valuable insights for businesses competing in the growing market of modern local coffee consumers.